Coagulation Process Followed SARS-Cov2 Infection and Vaccination - W. Issa, Yasir; M. Salih, Shahlaa; Khudhair, Ola (Al-Nahrain Journal of Science, 2024)
SARS-CoV-2, or COVID-19, a rapidly spreading coronavirus, leads to severe acute respiratory syndrome. In severe cases, hypercoagulability and inflammation significantly contribute to poor outcomes and mortality. This study investigated the coagulation process post-vaccination and infection in Iraq. A case-control study with 450 Iraqi participants included 90 healthy controls, 90 Pfizer vaccine recipients, 90 AstraZeneca vaccine recipients, 90 Sinopharm vaccine recipients, and 90 unvaccinated, infected individuals. Subgroups were followed up at 1, 2, and 3 months post-vaccination or infection to analyze plasma PT, PTT, INR, blood platelets, and D-Dimer. Significant differences were observed in D-Dimer levels among groups (p=0.000). Higher platelet counts were seen in infected patients, followed by AstraZeneca recipients (p0.05). COVID-19 severity correlates with fibrin and fibrinolytic activity. AstraZeneca recipients showed a higher risk of coagulation and fibrin formation compared to Pfizer and Sinopharm recipients, highlighting the potential need for anticoagulants to mitigate risks.